Effect of lavender aromatherapy mask on anxiety in the first stage of labour: - Intanwati; Mardiyono Mardiyono; Eny Retna Ambarwati; Melyana Nurul Widyawati (Jurnal Kesehatan Ibu dan Anak, 2022)
The anxiety experienced by most maternity mothers arises because of fear of pain. During a pandemic, relaxation with lavender aromatherapy requires innovation. The purpose of this study was to analyze the effect of using lavender aromatherapy masks on anxiety in the first stage of labour. The design of this study was a true experiment with a randomized controlled clinical trial. The intervention group wore lavender aromatherapy masks with a 100% concentration dose content of 0.08 ml for 120 minutes. The study sampled 40 samples.  The results of the study were that there was an effect of lavender aromatherapy masks on anxiety in the first stage of labour (p=0.000) with an effect size (d=1.319). Using a lavender aromatherapy mask can minimize the increase of anxiety during the first stage of labour.